2019
DOI: 10.1111/dth.12966
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects of omalizumab on peripheral blood cells and C‐reactive protein levels in patients with chronic spontaneous urticaria

Abstract: Omalizumab's mechanism of action is not well‐understood yet despite its strong therapeutic efficacy in chronic spontaneous urticaria (CSU). To determine the overall effect of omalizumab on peripheral blood cell counts and serum C‐reactive protein levels (sCRP) during a 1‐year follow‐up in patients with CSU. Data of 74 patients (male/female: 20/54) were reviewed from medical charts. Leucocyte counts, percentages of peripheral blood cells(lymphocyte, monocyte, neutrophil [PPBN], eosinophil, basophil [PPBB]) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
1
7
0
2
Order By: Relevance
“…In this study, leukocyte composition analysis showed the proportions of CD8 + T lymphocytes decreased in the CSU patients. Our results are consistent with those of a previous study (30,31). In our study, the percentage of granulocytes was significantly higher in the blood samples of the CSU patients than that in the blood samples of the healthy controls.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, leukocyte composition analysis showed the proportions of CD8 + T lymphocytes decreased in the CSU patients. Our results are consistent with those of a previous study (30,31). In our study, the percentage of granulocytes was significantly higher in the blood samples of the CSU patients than that in the blood samples of the healthy controls.…”
Section: Discussionsupporting
confidence: 93%
“…165 A study of 74 patients with CSU receiving omalizumab 300 mg every 4 weeks for at least 1 year resulted in a substantially increased peripheral blood basophil count and reduced peripheral blood neutrophil especially in the first 3 months. 166 The authors proposed that the alterations in peripheral blood cell ratios might contribute to or reflect the therapeutic effect of omalizumab in CSU. In another retrospective study of 74 patients with CSU receiving omalizumab 300 mg every 4 weeks, the neutrophil count, the neutrophil/lymphocyte ratio, and the neutrophil/monocyte ratio showed a statistically significant reduction after 12 weeks of omalizumab treatment.…”
Section: What Is the Clinical Relevance?mentioning
confidence: 99%
“…Omalizumab, a humanized monoclonal anti-IgE antibody, has been approved for the treatment of CSU (86,87). Notably, the omalizumab therapy rapidly increases the blood basophil number (88)(89)(90), whereas the number of FceRI + cells in skin lesions is decreased by omalizumab treatment (88). These results indicate the possibility that blood basopenia mirrors the recruitment of basophils to the skin lesion.…”
Section: Chronic Spontaneous Urticariamentioning
confidence: 99%